Cleaning and Corporate Management The Historical and Theoretical Relationship Between Japanese Companies and Their Cleaning Activities - Ohmori, Shin. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book provides a new way of understanding Japanese management by focusing on the relationship between Japanese companies and their social practices. Whereas previous studies have often concentrated on the uniqueness of Japanese companies' systems (e.g., lifetime employment, the seniority system, company-specific unions) or methods (e.g., bottom-up management, Toyota production methods), this book explains the uniqueness of Japanese companies' activities and practices. It especially highlights the day-to-day cleaning activities that many companies have practiced for numbers of years, regardless of their size or industry. Activities that continue beyond a certain period of time are called social practices, and the book clarifies how this particular social practice has historically been formed in Japanese companies and then shows what it means to keep cherishing those cleaning practices. This study consists of two parts: historical research and theoretical research. The historical research sheds light on the relationship between Japanese companies and cleaning activities from a historical point of view. On the basis of old literature and in-house documents, the reader can understand how Japanese companies have positioned cleaning practices in the process of increasing their growth potential and competitiveness and in maintaining their businesses. The second part explains theoretically the relationship between cleaning and management with quantitative and qualitative data from Japanese companies today. Using survey results from Japanese companies, the book shows what kinds of organizations will be formed and human resources will be developed if companies have been focusing for many years on 5S activities-Sort, Set in Order, Shine, Standardize, and Sustain- that include cleaning. This part of the book presents the distinctive problem-solving and strategy-creation processes of Japanese companies in contrast to the activities of European and American companies.
The Power of Cleaning: Factors Essential to Great Success in Business -- The Spirit of Toilet Cleaning: Escape from the Endless Competition for Differentiation -- The Spirit of Toilet Cleaning: How Leading Japanese Entrepreneurs Embraced It -- Two-fold Benefits: How to Gain Greater Utility from Cleaning -- Three Ways that Cleaning Strengthens Problem-Solving. .
Keywords: Management; Business ethics; School management and organization; School administration; Personnel management; Management; Business Ethics; Organization and Leadership; Human Resource Management